Atividade elétrica dos estabilizadores dinâmicos da patela no exercício de agachamento associado a diferentes posições do quadril em indivíduos normais e portadores de síndrome da dor femoropatelar - Say, Karina Gramani (Universidade Federal de São Carlos, 2005)
The purpose of this study was to evaluate the electrical activity of the Vastus Medialis Obliquus (VMO), Vastus Lateralis Obliquus (VLO) and Vastus Lateralis Longus (VLL) in the isometric wall slide squat exercise at 45 and 60º knee flexion associated in a neutral position (NP), 45º of lateral rotation (LR 45), 15º of medial rotation (MR 15) and 30º hip medial rotation (MR 30) only in the 45o angle. The electrical activity of the VMO, VLO and VLL of 15 healthy subjects control group (21,13 ± 2,17 years) and 12 subjects with Patellofemoral pain syndrome (PFPS) PFPS group (21,08 ± 2,31 years), female, was picked up using simple active differential surface electrode, the electromyography system of 8 channels and software Aqdados 7.2.6. The data were normalized by the percentage of the squatting exercise at 75º flexion and hip in neutral position RMS (µV). The volunteers executed the exercise on the Squat Platform that permitted the standing on the hip rotation desirable and the electrogoniometer indicated the amplitude of knee flexion. The ANOVA with repeated measures was used to analyze the data as well as the Duncan pos hoc (p≤0,05). The results of this study revealed no significant interaction between any knee angulation and hip position and every muscles showed significantly higher electrical activity at 60º squatting compared with 45º, on both groups. For the control group, intramuscles analysis, there was no statistical difference for hip position and intermuscles analysis, at 45º squatting as well as 60º, the VLL muscle showed greater electrical activity than VMO (p=0,00036 - 45º; p=0,02 - 60º) and VLO muscle (p=0,00013 - 45º; p=0,0048 - 60º), whereas there was no significant difference between the VMO and VLO muscle (p=0,68 - 45º; p=0,51 - 60º). For the PFPS group, in intramuscles analysis, just VLO muscle showed significantly difference to hip position (p=0,019), that this electrical activity greater in 60º LR (p=0,00); on the analysis between muscles it was revealed that, in 45º squatting, the VLL muscle showed significantly greater electrical activity than the VMO (p=0,005) and the VLO muscles (p=0,000), whereas, the VMO muscle showed greater electrical activity than VLO (p=0,0001). On the other hand, at 60º squatting, the electrical activity of VLL and VMO were greater than VLO muscle (p=0,000 VLL; p=0,0001 - VMO). However, there was no significative difference between VMO and VLL (p=0,72). The analysis between the groups revealed that just the VMO muscle of the PFPS groups showed greater electrical activity than VMO from the control group in 60º squatting with hip rotation analyzed, except in LR (p=0,00036). The results of this research, obtained under the experimental conditions, indicated that the squatting exercise at the 60º angle, in any hip position (except in the lateral rotation) is indicated for the PFPS treatment since it presents a higher stability of the medial and lateral components of the muscle (VMO and VLL). On the other hand, the squatting exercise at the 45º, in any hip position, should avoid in the subjects with PFPS because the electrical activity of VLL is higher than VMO.
Keywords: Sistema musculoesquelético; Agachamento; Articulação do joelho; Eletromiografia; Músculo quadríceps; Squat; Hip rotation; Patellofemoral pain Syndrome; Electromyography; Quadriceps muscle; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL